The Digital Transformation of Waqf Management: A Netnographic Study of Millennial Donors' Behavior in Indonesia - Amir Mukadar; Marini Marini (Tinta Emas Institute, 2023)
This study has analyzed millennial donor behavior within Indonesia’s digital waqf ecosystem using a netnographic approach. The study is grounded in the growing use of digital platforms for waqf mobilization and management, particularly among millennials who routinely conduct financial, social, and religious activities through online media. Data were collected from five digital field sites: Instagram, Twitter/X, Kitabisa, Wakaf.com, and YouTube. The dataset consisted of 3,379 data units, including posts, comments, donor responses, campaign updates, and public interactions. The data were analyzed using reflexive thematic analysis to identify patterns of behavior, motivation, trust construction, and digital accountability in online waqf practices. The findings reveal three major themes: platform-mediated trust construction, gamified Islamic giving, and the formation of digital waqf communities as spaces of religious identity and social accountability. Donor trust was found to depend not only on institutional reputation, but also on visual transparency, Sharia legitimacy, managerial responsiveness, and the influence of digital religious figures. The study also identifies an ethical tension between the effectiveness of digital campaign strategies and the Islamic value of sincerity in giving. Overall, the study concludes that digital waqf has significant potential to expand youth participation in Islamic philanthropy, but its success depends on the integration of platform innovation, transparent governance, waqf literacy, and religious ethics.